Conflict Economies, Forced Migration, and Livelihood Adaptation in Zamfara State, Nigeria: Examining the Impact of Gold Mining and Banditry - Terwase Shabu; Folashade Florence Daodu (International Journal of Education, Culture, and Society, 2026)
Conflict economies have emerged in regions where political instability, armed conflict, and weak governance create space for informal and illegal economic activities, with significant implications for forced migration and livelihood systems. This study examines the interrelationship between conflict economies, forced migration, and livelihood strategies in Zamfara State, Nigeria, with particular focus on gold mining and banditry or kidnapping. The study employed a multistage sampling procedure to ensure adequate representation of the study population. Purposive sampling was used to select local government areas with gold-mining activities, and 142 respondents were drawn from internally displaced persons camps in the selected areas. Data obtained through fieldwork and archival records were analyzed using descriptive statistical techniques, including percentages, frequencies, and distribution tables. The findings reveal that corruption (71.8%) constitutes the most prominent economic driver of conflict, while state actors, especially military forces (54.9%), play a significant role in the conflict economy. Among non-state actors, criminal organizations were identified as the dominant group, accounting for 43.7% of responses. The results further show that agriculture remains the principal livelihood source, with 49.3% of respondents identifying it as their primary occupation, although livelihood systems were generally perceived as weakly adaptive, with none of the respondents rating them as extremely adaptable and only 2.8% considering them adaptable. Financial support programmes (39.4%) emerged as the most prioritized policy response, underscoring the importance of direct economic interventions for livelihood recovery. The study concludes that conflict economies and forced migration significantly disrupt livelihood strategies in Zamfara State, with gold mining and banditry at the center of these challenges. These findings contribute to understanding the socio-economic consequences of conflict in resource-rich but insecure settings and highlight the need for coordinated interventions aimed at curbing illegal economic activities, strengthening governance, promoting peacebuilding, and restoring sustainable livelihoods for long-term stability and resilience.